Tsangaya: The Traditional Islamic Education System in Hausaland - Ahmad Yahya (Jurnal Pendidikan Islam, 2018)
In the pre-colonial Hausaland, an Islam-based educational system existed for several centuries and had produced leaders, scholars, businessmen, government functionaries, etc. This paper taking Kano as its focus of attention, and generating data through personal discussions, interviews, document analysis and personal experience, examines the Tsangaya system with the aim of bringing light into its untold beautiful features which are from a leaf that could be borrowed and successfully used in the so-called formal system. The paper reveals that the Tsangaya had staged from elementary to advanced and had its distinct of pedagogy and at the top of which there is educational delivery. Some benefits of the Tsangaya found in this study such as the strong relationship between teacher and student, respect for knowledge either for students or teacher, blending activities between teaching and learning and daily morality that can be useful for the modern era.